Performance and Energy Consumption Evaluation of Rotating Biological Contactor for Domestic Wastewater Treatment - Sharjeel Waqas; Muhammad Roil Bilad; Zakaria B Man (Universitas Pendidikan Indonesia, 2021)
Biological processes are extensively used for wastewater treatment because of low organic footprint, economically feasible, and high treatment efficiency. Rotating biological contactors (RBC), an attached growth biological process offers advantage of low operating cost, simple configuration and structure, reduced bionomical footprint and thus has been extensively employed for organics and nitrogen removal. In this study, RBC was used for the treatment of synthetic domestic wastewater operating at high hydraulic and organic loading rate to demonstrate the biological performance. The results showed that the RBC achieved a treatment efficiency for COD, ammonium, TN and turbidity of 70.2%, 95.2%, 70%, and 78.9 %, respectively. The efficient nitrogen removal and increased nitrate concentration signify the presence of nitrifying bacteria which actively degrade the nitrogen compounds through the nitrification process. Thus, this system is a sound alternative for both domestic and industrial wastewater treatment for decentralized applications.